School bullying by one or more ways : does it matter and how do students cope? - Skrzypiec, Grace (2011)
Students (n=452; ages 12–14 years) attending two South Australian metropolitan high schools completed the ‘Living & learning at school: Bullying at school’ survey in which they reported ways they were bullied and the strategies they would use to deal with bullying. Results showed that a small proportion of students were bullied in three or more ways, and that males and females differed in the coping strategies they would use if bullied. Significant differences were found between bullied and not bullied students in their use of ‘problem-focused’ in contrast to ‘emotion focused’, or ‘approach’ in contrast to ‘avoidance’ coping strategies, with bullied students more likely to use ‘avoidance’ strategies. Findings suggest that in terms of coping, it does matter whether or not a student is bullied in multiple ways.